Penta-O-Galloyl-β-D-Glucose in Pistacia integerrima Targets AMPK-ULK1 and ERK/STAT3 Signaling Axes to Induce ROS-Independent Autophagic Cell Death in Human Lung Cancer Cells - Balkrishna, Acharya; Mulay, Vallabh Prakash; Verma, Sudeep; Srivastava, Jyotish; Lochab, Savita; Varshney, Anurag (Frontiers in Pharmacology, 2022)
Natural molecules have promising perspectives as adjuvants to chemotherapies against cancer. Pistacia chinensis subsp. integerrima (hereafter, Pistacia integerrima) traditionally known for medicinal values in respiratory disorders was tested for anti-lung cancer properties. The extract prepared from Pistacia integerrima (PI) selectively impaired the viability of lung cancer cells, A549 and NCI-H460 compared to non-cancer cells. At non-lethal concentrations, PI mitigated colony-forming, spheroid formations, and metastatic properties of lung cancer cells. As a step toward identifying the phytomolecule that is imparting the anti-lung cancer properties in PI, we subjected the extract to extensive characterization through UPLC/QToF-MS and further validated the findings with UHPLC. The gallotannin, Penta-O-Galloyl-β-D-Glucose (PGG), among others, was identified through UPLC/QToF-MS. PGG exhibits potential chemopreventive effects against various cancer types. However, a defined mechanism of action of PGG in restricting lung cancer progression is still unexplored. Bioactivity-guided column fractionations enabled the determination of PGG as the major phytochemical that governed PI-mediated AMPK-ULK1-dependent autophagy and apoptosis, albeit independent of intracellular ROS activation. Interestingly, the autophagy flux when inhibited restored the cell viability even in the presence of PI. The study further delineated that PI and PGG activated ERK, and inhibited STAT3 activation to trigger apoptosis through caspase-3 and PARP 1 pathways. Collectively, the findings demonstrate that PGG propels the PI to effectively combat lung cancer progression through autophagic cell death by altering ERK/AMPK-ULK1/STAT3 signaling axes. The study proposes PGG as a potential AMPK activator and STAT3 inhibitor that can be exploited further in developing adjuvant chemotherapeutics against lung cancer.